2021
DOI: 10.1055/a-1386-3912
|View full text |Cite
|
Sign up to set email alerts
|

Management of Intrahepatic Cholestasis of Pregnancy: Recommendations of the Working Group on Obstetrics and Prenatal Medicine – Section on Maternal Disorders

Abstract: Intrahepatic cholestasis of pregnancy (ICP) is the most common liver disease specific to pregnancy. The cardinal symptom of pruritus and a concomitant elevated level of bile acids in the serum and/or alanine aminotransferase (ALT) are suggestive for the diagnosis. Overall, the maternal prognosis is good. The fetal outcome depends on the bile acid level. ICP is associated with increased risks for adverse perinatal outcomes, including preterm delivery, meconium-stained amniotic fluid, and stillbirth. Acute fetal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
14

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 153 publications
0
18
0
14
Order By: Relevance
“…GO analysis showed that the exosomal proteins in patients with ICP were enriched in cellular process, biological regulation, response to stimulus, metabolic process, localization, immune system process, etc., suggesting that a combination of genetic disposition and hormonal and environmental factors favours ICP onset. ICP is caused by impaired hepatobiliary transport resulting in the retention of substances that are physiologically excreted with bile [9]. ICP is recognized to be associated with an abnormal metabolic pro le [26], including glucose intolerance and dyslipidaemia, although it is considered to be secondary to aberrant maternal bile acid homeostasis, in which biological regulation, response to stimulus, and metabolic process play pivotal roles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GO analysis showed that the exosomal proteins in patients with ICP were enriched in cellular process, biological regulation, response to stimulus, metabolic process, localization, immune system process, etc., suggesting that a combination of genetic disposition and hormonal and environmental factors favours ICP onset. ICP is caused by impaired hepatobiliary transport resulting in the retention of substances that are physiologically excreted with bile [9]. ICP is recognized to be associated with an abnormal metabolic pro le [26], including glucose intolerance and dyslipidaemia, although it is considered to be secondary to aberrant maternal bile acid homeostasis, in which biological regulation, response to stimulus, and metabolic process play pivotal roles.…”
Section: Discussionmentioning
confidence: 99%
“…To date, no uni ed ICP diagnostic criteria have been developed, and the cardinal symptoms of pruritus and jaundice and a concomitant elevated level of serum levels of total bile acids (TBA) (≥ 10 µmol/L) and/or alanine aminotransferase (ALT) are considered suggestive for diagnosis in China [8,9]. The diagnosis should exclude other clinical entities of chronic liver disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first-line treatment is the administration of ursodeoxycholic acid (UDCA) 15 mg/kg/day (not assigned an FDA pregnancy category) [105]. Although the PITCH study published in 2019 in The Lancet [106] suggested that UDCA may not be effective in preventing stillbirth, the newly published guidelines (2021) [107] highlighted weaknesses of the PITCH study (the administered dose of UDCA was not taken into consideration) and advocated for the use of UDCA in this group of patients. The role of the synergistic effect of rifampicin 300-1200 mg (FDA pregnancy category C) on bile acid clearance in severe ICP (bile acids > 100 µmol/l) is still being discussed [108][109][110][111] and should be considered when there is no improvement with UDCA alone.…”
Section: Treatmentmentioning
confidence: 99%
“…Didelis INC paplitimas stebimas Azijos valstybėse (ypač Indijoje, Pakistane). Australijoje ligos pasireiškimo dažnis siekia 0,7 procento [5,6]. INC dažniau atsiranda vyresnio amžiaus nėščiosioms (> 35 m.), esant daugiavaisiam nėštumui, sergant lėtine kepenų liga (pvz., lėtinis hepatitas C, nealkoholinė kepenų cirozė), taikant pagalbinį apvaisinimą [7,8].…”
Section: Tyrimo Rezultatai Ir Jų Aptarimasunclassified